Międzynarodowe aspekty obywatelstwa - Czapliński, Władysław (Wydział Prawa i Administracji UAM, 1984)
Citizenship as a relationship of individual and State developed in Europe at the end of 18 century. There is a controversy in the doctrine whether it is an institution of international or internal law. I general two aspects of the institution can be differentiated — citizenship in a sphere of internal law and nationality in the sphere of international law. A general principle was adopted in international practice that each state can freely regulate its nationality, the liberty of that regulation is however limited by international law, especially by customary norms. Existence of nationality is not related to passing a relevant act of internal law by a State nor is the method of regulation adopted in a given State significant. In practice there are two basic means formed of acquisition of nationality at a moment of birth: according to ius soli or ius sanguinis. A possibility of naturalization is also warranted by respective legal systems, while acquisition and loss of nationality by means of legal transactions of private law is of a slight importance. Basic means of a loss of nationality are: renouncement and- in exceptional, precisely defined situations in internal law of respective states deprivation of nationality. Application of those institutions can presently be limited by provisions of international law concerning protection of human rights and and precluding cases of dual nationality and statelessness. Nationality is an individual status. Change of nationality related to change of sovereign of a given State (succession of states) is of an exceptional character. There was a principle developed in practice that persons inhabiting an area which is changing its sovereign and possessing nationality of his predecessor are automatically loosing their previous nationality and acquiring the nationality of the successor. A duty to guarantee the option is not adoptod in modern international law. Conflicts of legislations on nationality of many states can result in dual nationality or statelessness. Presently actions are undertaken in order to eliminate those situations and diminish their effects. In practice, a person posessing a dual nationality is treated by the third state as a national of one state only. Stateless persons are granted a minimum standard of treatment by the international agreements. The international practice, especially the ICJ decision in the case of Nottebohm confirmed the existence of customary norm providing that an effective relation of an individuai and a State is a prerequisite of effective acquisition of nationality by persons nationals of only one state. That requirement is to preclude fictitious granting of nationality and to secure international community against infringement of international law and abuse of nationality for illegal goals.
Aspects of nationality in international law